Rh Blood Group Positive Newborn of Rh Blood Group Negative Parents, Why, and How? - Yahya Ethawi; Mona Kahalf; Rola Al Zir (Al-Anbar Medical Journal)
The proteins of Rhesus (Rh) antigens are transmembrane proteins. The main antigens are D, C,E, c, and e, which are encoded by two adjacent gene loci. The presence or absence of RhD allele ina person is typed either positive or negative, represents by a suffix (+/-) after the ABO type. Theantigenicity of Rh antigen is guarded by many factors, for example, the molecular weight of theantigen and the antigen being accessible to the antibody. Rh phenotypes can be identified by thepresence or absence of the Rh surface antigens. The Rh antigen protein represented by 2 allelesat the specific gene locus. Rh-negative positive person can be homologous have 2 RhD alleles orheterozygous having RhD and Rhd alleles. Therefore, Rh positive parents can have Rh-negativechildren if both are Rh heterozygous. At the same time, Rh negative parent can have Rh positivechildren if both parents genotypically are positive but phenotypically are negative. They will testnegative on antigenicity testing but on DNA testing they are actually RhD positive. Thus theywill give the allele to their baby. If the baby expressed the RhD antigen on the surface will bephenotypically and genotypically positive.